HUBUNGAN ANTARA FAKTOR SOSIAL DEMOGRAFI DENGAN PERILAKU PETANI DALAM MENGAPLIKASI PESTISIDA - Kasman Jaya; Sayani; Ratnawati; Rastam (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to determine the relationship of social domographic factors with the behavior of farmers in applying pesticides to shallots in Sigi Biromaru District, Sigi Regency. This research uses quantitative methods using univariate analysis for frequency distribution and bivariate analysis (chi square) to determine the correlation between variables. Both use Statistical Product and Service Solutions (SPSS) 20.0. Determination of the location of the study was conducted purposively based on previous observations. The area is a center of shallot and horticulture plants in Sigi Regency, namely; Oloboju Village and Bulupountu Village, Sigi Biromaru District. The results of the study concluded that the use of pesticides by shallot farmers was over intensity with the reason for maximum production results. Unwise behavior of farmers in controlling pests and diseases with the high use of pesticides in the field, shows that there is no relationship between age, education, experience and Integrated Pest controlling (IPC) training with the behavior of shallot farmers in applying pesticides.